Analisis Kualitatif Preferensi dan Nilai Konsumsi Kopi pada Generasi Urban di Kecamatan Medan Petisah - Azwana Azwana; Rahma Sari Siregar (Mahesa Research Center, 2026)
This study aims to analyze the preferences and value of coffee consumption in the urban generation in Medan Petisah District, Medan City, North Sumatra. The research focuses on consumer preferences toward coffee product attributes (type, taste, and aroma) as well as the stages of the purchasing decision-making process. A qualitative approach was employed, with data collected through in-depth interviews using purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that consumer preferences are primarily influenced by taste and aroma, followed by coffee type and café atmosphere. Adolescents and young adults tend to prefer modern coffee variants with sweet and creamy flavors, while older consumers maintain a preference for stronger and more bitter traditional coffee. In the decision-making process, consumers go through stages of need recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior. Social reference groups and social media play a significant role in the information search stage, whereas post-purchase satisfaction is determined by the alignment between taste quality, café ambiance, pricing, and consumer expectations. The study concludes that coffee consumption behavior is driven not only by functional needs but also by social, emotional, and lifestyle factors. Therefore, café marketing strategies should emphasize product differentiation, consistency in taste and aroma quality, a comfortable and appealing atmosphere, and community-based promotional approaches to enhance customer satisfaction and loyalty.